Risk factors for the development of interstitial lung disease following severe COVID-19 pneumonia and outcomes of systemic corticosteroid therapy: 3-month follow-up: Interstitial lung disease following severe COVID-19 pneumonia - Günay, Sibel; Parlak, Izzet Selcuk; Hezer, Habibe; Şeref Parlak, Ebru Şengül; Umut, Melike Sanem; Hancıoğlu, Zeynep; Çelenk Ergüden, Hülya; Kocaman, Yasin; Dalkıran, Aynil; Sertçelik, Ümran; Şerifoğlu, İrem; Akpınar, Esmehan; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background:We aimed to evaluate the pulmonary involvement status, its related factors, and pulmonary function test (PFT) results in the first month follow-up in patients who were discharged for severe Covid-19 pneumonia, and to assess the efficacy of corticosteroid treatment on these parameters in severe pulmonary involvement patients.Methods:We retrospectively analyzed all consecutive patients who applied to our COVID-19 follow-up clinic at the end of the first month of hospital discharge. Functional and radiological differences were compared after 3 months of corticosteroid treatment in severe pulmonary involvement group.ResultsWe analyzed 391 patients with “pulmonary parenchymal involvement” (PPIG) and 162 patients with “normal lung radiology” (NLRG). 122 patients in the PPIG (corticosteroid-required interstitial lung disease group (CRILD)) had severe pulmonary involvement with frequent symptoms and required corticosteroid prescription. Pulmonary involvement was more common in males and elder patients (P